Prevalence of and factors associated with tobacco smoking in the Gambia: a national cross-sectional study - Abu Naser Zafar Ullah; Md Shariful Islam; Md Golam Rabbani; Haifaa AlWajeah; Md Ferdous; Nusrat Sharmin Mahfuza; Daniel Konka; Eva Silenga (BMJ Open)
Objectives To examine the prevalence of and risk factors associated with tobacco smoking in the Gambia.Design A nationwide cross-sectional study.Setting The Gambia.Participants The study participants were both women and men aged between 15 and 49 years old. We included 16,066 men and women in our final analysis.Data analysis We analysed data from the Gambia Demographic and Health Survey (DHS), 2019–2020. DHS collected nationally stratified data from local government areas and rural–urban areas. The outcome variable was the prevalence of tobacco smoking. Descriptive analysis, prevalence and logistic regression methods were used to analyse data to identify the potential determinants of tobacco smoking.Results The response rate was 93%. The prevalence of current tobacco smoking was 9.92% in the Gambia in 2019–2020, of which, 81% of the consumers smoked tobacco daily. Men (19.3%) smoked tobacco much higher than women (0.65%) (p<0.001). People aged 40–49 years, with lower education, and manual workers were the most prevalent group of smoking in the Gambia (p<0.001).Men were 33 times more likely to smoke tobacco than women. The chance of consuming smoked tobacco increased with the increase of age (adjusted OR (AOR) 9.08, 95% CI 5.08 to 16.22 among adults aged 40–49 years, p<0.001). The strength of association was the highest among primary educated individuals (AOR 5.35, 95% CI 3.35 to 8.54).Manual workers (AOR 2.73) and people from the poorest households (AOR 1.86) were the risk groups for smoking. However, place of residency and region were insignificantly associated with smoking in the Gambia.Conclusions Men, older people, manual workers, individuals with lower education and lower wealth status were the vulnerable groups to tobacco smoking in the Gambia. Government should intensify awareness programmes on the harmful effects of smoking, and introduce proper cessation support services among tobacco smoking users prioritising these risk groups.